African Initiated Christianity and the Decolonisation of Development Sustainable Development in Pentecostal and Independent Churches - Öhlmann , Philipp; Gräb, Wilhelm; Frost, Marie-Luise (Routledge Research in Religion and Development, 2020)
This book investigates the substantial and growing contribution which African Independent and Pentecostal Churches are making to sustainable development in all its manifold forms.